Kekerasan Seksual Sebagai Taktik Perang Kongo: Antara Impunitas Hukum Nasional dan Pemberlakuan Statuta Roma - Udit, Indah Ardhita; Novianti, Novianti; Harahap, Rahayu Repindowaty (Uti Possidetis: Journal of International Law, 2021)
Sexual violence during conflict has become a crucial issue in the realm of Humanitarian Law. In its development, this form of violence is carried out systematically, spreads, and is often carried out under orders. This article discusses how the enforcement of humanitarian law can be implemented properly in the Congo war. The results of the study show that the effectiveness of Congo's national law should have played a role in this incident. Weak national law enforcement results in the failure of the function of law as a guide to justice, resulting in impunity. As a preventive measure, the implementation of the Rome Statute is imperative. The statute states that systematic and widespread sexual violence is a form of crime against humanity and a violation of humanitarian law.